Cistercian architecture and medieval society - Sternberg, Maximilian, 1979- (Brill's studies in intellectual history ;, 2013)
In Cistercian Architecture and Medieval Society Max Sternberg offers an account of the social functions of the built environment in medieval monasticism, focusing in particular on the white order of the Languedoc in the 13th century.